"Just keep pushing": Parents' experiences of accessing child and adolescent mental health services for child anxiety problems. (27th May 2019) - Crouch, Lauren; Reardon, Tessa; Farrington, Alice; Glover, Frankie; Creswell, Cathy
Abstract: Background: Anxiety disorders are among the most common psychopathologies in childhood; however, a high proportion of children with anxiety disorders do not access effective treatments. The aim of the present qualitative study was to understand families' experiences of seeking help and accessing specialist treatment for difficulties with childhood anxiety. Methods: Parents of 16 children (aged 7–12 years) referred to a child mental health service for difficulties with anxiety were interviewed about their experiences of seeking and accessing treatment within Child and Adolescent Mental Health Service (CAMHS). All interviews were transcribed verbatim and thematically analysed for similarities and differences in families' experiences. Results: Factors that helped and/or hindered families accessing treatment related to (a) parental recognition, (b) contact with professionals, (c) reaching CAMHS, (d) parental effort, and (e) parental knowledge and concerns. High demands on services and parents' uncertainty surrounding the help‐seeking process presented key hurdles for families. The critical role of parental persistence and support from general practitioners and school staff was evident across interviews. Conclusions: Findings highlighted the need for information and guidance on identifying child anxiety difficulties and professional, peer, and self‐help support, and ensuring sufficient provision is available to allow families prompt access to support.